Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.4 The Product and Quotient Rules - 3.4 Exercises: 47

Answer

$g'(x)= \frac{1-3x}{e^{3x}}$

Work Step by Step

$g(x)=\frac{x}{e^{3x}} = (x)(e^{-3x})$ Using Product Rule and $\frac{d}{dx}e^{nx} = ne^{nx}$ $g'(x)=(1)(e^{-3x})+(x)(-3e^{-3x}) = \frac{1}{e^{3x}} - \frac{3x}{e^{3x}} = \frac{1-3x}{e^{3x}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.